Service Quality Challenges and Strengths in a Remote Public Health Center: Tantangan dan Keunggulan Kualitas Layanan di Pusat Kesehatan Masyarakat Jarak Jauh - Ului, Martinus; Sabil, Ibnu; Priyanto, Agus (Indonesian Journal of Innovation Studies, 2026)
General Background: Quality primary healthcare services are essential in meeting increasing public expectations, particularly in remote regions. Specific Background: At the Sungai Boh Community Health Center, previous surveys reported low satisfaction scores, indicating persistent service quality issues. Knowledge Gap: Despite known challenges, empirical analysis across the SERVQUAL dimensions in remote health facilities remains limited. Aims: This study analyzes the quality of health services at the Sungai Boh Health Center based on five SERVQUAL dimensions: reliability, responsiveness, assurance, empathy, and tangibles. Results: Findings reveal that responsiveness and empathy are relatively strong, supported by staff commitment and routine training; however, service reliability and assurance are hindered by infrastructural limitations, incomplete medical equipment, and inconsistent discipline. Tangible aspects such as waiting areas and diagnostic tools remain inadequate. Novelty: This study demonstrates how geographical isolation interacts with human resource capacity and infrastructural constraints to shape service quality outcomes within a rural Indonesian health center. Implications: Improvements in supporting facilities, continuous professional development, strengthened SOP implementation, and enhanced coordination with local health authorities are required to ensure efficient, equitable, and patient-centered healthcare delivery in remote areas. Highlights:  Strong responsiveness and empathy improve patient trust despite limited resources. Infrastructural and equipment gaps remain major barriers to service reliability. Continuous training and strengthened SOPs are crucial for sustaining quality care. Keywords: Health Service Quality, Servqual, Primary Healthcare, Patient Satisfaction, Remote Health Centers